TERMINOLOGIA EM CONTEXTOS INTEGRADORES: FUNCIONALIDADE E FUNDAMENTOS - Krieger, Maria da Graça (Organon, 2012)
This paper aims to reflect on the role and relevance of terminology on the consolidation process of theeconomical, cultural and scientific integration in supra-regional contexts. The prominence given to terminology in itscommunicative and social dimension is contextualized in the reality of Mercosul. The theoretical and methodologicalfundamentals which support a terminographic project with an effective practical scope will also be emphasized.Additionaly, some investigation subjects, issues which are vital to the advance of a terminological theory based oncommunicational linguistics are pointed out.